3D printing of SiC ceramic: Direct ink writing with a solution of preceramic polymers. Issue 16 (December 2018) - Chen, Hehao; Wang, Xiaofeng; Xue, Fengdan; Huang, Yujuan; Zhou, Kechao; Zhang, Dou
Abstract: 3D structured SiC ceramics with varying feature sizes (100–400 μm) were achieved by direct ink writing of polycarbosilane (PCS)/ n -hexane solution. The rheological properties of the PCS solution and printing parameters were tailored for optimum writing behaviour. The integrity and clear surface of the filaments indicated the printing ability of forming the self-supporting features along with the rapid evaporation of solvent. As-printed 3D structured PCS was processed by oxidative crosslinking and pyrolysis and converted to SiC ceramic. Although strong shrinkage occurred during the pyrolysis, SiC ceramic maintained the original 3D structure. Both proper viscoelasticity of printable solutions and the homogeneous shrinkage in the pyrolysis determine the integrity and feature characteristic of 3D structured SiC using direct ink writing preceramic polymer.